The role of power in community participation: Relocation as climate change adaptation in Fiji - Bertana, Amanda (Environment and Planning C: Politics and Space, 2020)
As the impacts of climate change intensify, potential relocation is becoming more of a reality for coastal communities throughout the world. This is furthering the demand for the implementation of governance relocation frameworks. In order to stay true to the principles of environmental justice while at the same time ensuring an effective policy that meets the needs and wants of affected communities, an adaptive relocation framework requires collaboration between state and non-state actors. It is thus important to pay attention to how non-state actors are incorporated into public participatory climate change adaptation efforts. In order to affectively address previous limitations of public participation, stakeholders must pay attention to already existing power systems. Through a case study approach of a village relocation project in Fiji, I examine the role of power in a climate change adaptation plan that involved the community of Vunidogoloa, local government, and national government stakeholders. I employ Steven Lukes’s three-dimensional framework of power to the case of Vunidogoloa, a Fijian village that relocated inland due to coastal erosion and shoreline flooding, to illustrate how the political arrangement of participation reinforced existing hierarchies between the village and the government.
Keywords: dept.soc; peer-reviewed

Gender-collaborative training in elite university sport: Challenging gender essentialism through integrated training in gender-segregated sports - Ogilvie, M. F.; McCormack, Mark (International Review for the Sociology of Sport, 2020)
Competitive teamsport at university level is predominantly segregated by gender in many western countries, despite concerns that gender segregation in sport can perpetuate sexism and gender inequality. While policies and activities seek to challenge sexism and gender inequality, the use of gender collaboration within a gender-segregated system as a method to achieve this has received little attention. In this article, we draw on a year-long ethnography of elite sport and 48 in-depth interviews with elite male and female athletes at a British university to explore the impact of various forms of gender mixing during training, which we call ‘gender-collaborative training’. While men’s and women’s teams competing against each other in practice matches resulted in gender-essentialist narratives attributing difference to biology, gender-integrated practices and workouts provided opportunities for men and women to train together without the gendered sport-specific associations that can reproduce sexism. We call for gender-collaborative training to be adopted by gender-segregated teams, and suggest that where there is resistance to any integration, teams start with mixed physical workouts and progress to mixed sport-specific training and then mixed competitive training. © The Author(s) 2020.
Keywords: adult; article; dept.soc; ethnography; female; human; interview; male; narrative; peer-reviewed; sexism; training

“Dad, wash your hands”: Gender, care work, and attitudes toward risk during the COVID-19 pandemic - Umamaheswar, Janani; Tan, Catherine (Socius: Sociological Research for a Dynamic World, 2020)
Recent analyses of responses to coronavirus disease 2019 (COVID-19) have posited that men’s dismissive attitudes toward the risks of the virus reflect their attempts to conform to masculine norms that valorize bravery and strength. In this article, the authors develop an alternative account of the gender differences in attitudes toward COVID-19. Drawing on three waves of in-depth interviews with college students and members of their households (n = 45) over a period of 16 weeks (for a total of 120 interviews), the authors find that men and women in comparable circumstances perceive similar risks of COVID-19, but they diverge in their attitudes toward, and responses to, these risks. Connecting scholarship on gender and care work with research on risk, the authors argue that gender differences in attitudes toward risk are influenced by the unique and strenuous care work responsibilities generated by the COVID-19 pandemic, which are borne primarily by women—and from which men are exempt. © The Author(s) 2020.
Keywords: COVID-19; care work; dept.soc; gender; pandemic; peer-reviewed; risk perception

The impact of faith-based narratives on climate change adaptation in narikoso, fiji - Bertana, Amanda (Anthropological Forum, 2020)
Most research on climate change in South Pacific island communities has privileged people’s observations of physical environmental change with less attention paid to how people interpret the causes of these changes. Increasingly, more studies are focusing on how communities are receiving messages about environmental degradation, and from whom they are receiving them. This case study draws upon ethnographic research conducted in November 2015 in Narikoso on Ono Island in Fiji’s Kadavu Group. This village was in the process of relocating inland as a response to shoreline erosion and severe coastal flooding. By employing data drawn from interviews with government actors, religious leaders, and residents of Narikoso village along with fieldnotes from participant observation, this paper examines how village residents interpreted coastal flooding and shoreline erosion according to the biblical story of Noah’s Ark alongside a secular narrative of climate change. I conclude by showing the unique challenges these worldviews had on the community’s decision to relocate. © 2020 The University of Western Australia.
Keywords: Fiji; Relocation; climate change adaptation; dept.soc; peer-reviewed; religion; sea level rise

“When the hell are you going to grow up?”: a life-course account of hybrid masculinities among incarcerated men - Umamaheswar, Janani (Journal of Developmental and Life-Course Criminology, 2020)
Purpose: Recent life-course scholarship has argued that desistance from (rather than persistence in) crime is a marker of adulthood. In this article, I argue that a commitment to desistance is only one of many elements of the participants’ sense of adult masculinity, which is best understood by drawing on theoretical literature on “hybrid masculinities.” By linking life-course criminological literature with recent theoretical advancements in the sociology of gender, I connect two important, but as yet independent, strands of research. Methods: Using the grounded theory approach to qualitative research, I performed inductive analyses of 24 in-depth interviews with adult men incarcerated at a state-run facility in the Northeastern USA. Results: I argue that the participants construct hybrid masculinities that combine conventionally masculine traits (such as being a provider and protector) with conventionally feminine traits (such as loyalty, humility, and emotional expressiveness). These hybrid masculinities manifest through the participants’ reliance on intangible markers of adulthood, and they emerge gradually over the men’s life course. I further argue that the disruptions that incarceration poses to the men’s life course impede their ability to realize their hybrid masculinities fully. Conclusion: The current research contributes to the burgeoning literature that attempts to correct the oversimplified portrayal of incarcerated men as singularly hypermasculine, and it also highlights how incarceration disrupts men’s life course, making it difficult for them to be the “hybrid” men that they wish to be. © 2020, Springer Nature Switzerland AG.
Keywords: Hybrid masculinity; Incarceration; Masculinity; Prison; The life course; dept.soc; peer-reviewed